Peningkatan Kinerja Guru IPA Dalam Mengimplementasikan Standar Proses Melalui Pendampingan Sejawat (Peer Coaching) Di Kabupaten Kutai Barat - Muslikin; Makrina Tindangen; Afif Ruchaemi (LP. Ma'arif Janggan Magetan, 2021)
The objective of the research is to improve the performance of junior high school science studies teacher (SMP) in implementing the Standard Process as part of National Standards of Education through Mentoring Program MGMP MKKS by applying the model of peer coaching. This research was conducted in Dinas Pendidikan Kab. Kutai Barat involving five junior high schools joined in the activities MGMP MKKS IPA teachers in Kab. Kutai Barat. Implementation of peer coaching held in five SMP: SMP Negeri 1 Bongan, SMP Negeri 2 Jempang, SMP Negeri 2 Muara Pahu, SMP Negeri 4 Sendawar, dan SMP Negeri 1 Sendawar. This research use both quantitative and qualitative approach. The research was conducted by using model of Kemmis & Mc Taggart combined with the peer coaching model developed by Ng Pak Tee. The result of this research are: implementation of peer coaching can improve the performance of teachers in the planning, implementation, and assessment of learning in the learning process, peer coaching program will increase the quality of education and learning become more meaningful for students. DOI: https://doi.org/10.33399/edukasia.v2i1.29